The Effects of Garlic Oil and Tartaric Acid on the Quality of Shrimp Stored at 4°C - Md Noordin, Wan Norhana; Shunmugam, Nannthini; Adzitey, Frederick; Huda, Nurul (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
The objectives of this study were to determine the effects of garlic oil (GO) and tartaric acid (TA) on microbiological, pH, and Thiobarbituric Acid Reactive Substances (TBARS) (lipid peroxidation) of shrimp stored at 4°C. Shrimp of 2 kg were dipped in GO and TA solutions at 1:2 shrimp/treatment solutions (w/w) for 30 min under 25ºC. Sodium metabisulfite (MBS) and sterile distilled water (dH20) were used as positive and negative controls, respectively. Shrimp were drip-dried for 5 min, packaged, and stored in a chiller (4°C) for 10 days. The shrimp were analysed on days 0, 3, 5, 7, and 10. Total aerobic plate count, psychotropic bacteria count, Listeria monocytogenes, Salmonella enterica serovar Typhimurium (S. Typhimurium) and Vibrio parahaemolyticus counts ranged from 3.52-8.73 log CFU/g, 3.30-5.16 log CFU/g, 3.48-7.60 log CFU/g, 3.42-6.34 log CFU/g and 3.48-5.55 log CFU/g, respectively. The pH of shrimp ranged from 6.64 to 8.03. The pH of shrimp dipped in MBS (7.70) and TA+GO (7.70) was lowest at the end of storage period. TBARS values ranged from 0.70-2.66 and TBARS values for shrimp treated with MBS (1.83) were lowest at day 10. In general, microbiological counts, pH and TBARS values of sample treated with TA+GO increased with storage time, however comparable to MBS. Treatment of shrimp with GO and TA could inhibit the growth of foodborne pathogens. The pH of the test and control shrimp were similar on day 10. Lipid peroxidation was lowest for TA and MBS treated shrimp by day 10.